Double Standards: The Role of Techniques of Neutralization - De Bock, Tine (Journal of business ethics, 2011)
Despite the growing number of studies examining consumers’ perceptions of unethical corporate and consumer practices, research examining the apparent double standard existing between what consumers perceive as acceptable corporate behaviour and what they believe are acceptable consumer practices remains scarce. Contradictory, double standards are often quoted by other researchers as a major stream in ethical literature. The few studies dealing with this topic as well as this study indicate that people rate corporate unethical actions as less admissible compared to similar consumer misactions. However, little is known about the processes underlying these double standards. This research investigates whether the techniques of neutralization could provide a meaningful way of approaching this phenomenon. Findings indicate that the higher the extent to which people agree with arguments explaining away the misbehaviour instigated by consumers or business, the more they tolerate these questionable consumer and corporate practices. Furthermore and more importantly, these techniques give an answer on the question why people judge business (representatives) more harshly than consumers. More specifically, results show that the same respondents who justify questionable consumer actions to a certain degree, condone the same misbehaviours instigated by business (representatives) to a much lesser extent. In this way, the techniques of neutralization concern a process explaining the double standard phenomenon.